Elevated levels of plasma mitochondrial DNA DAMPs are linked to clinical outcome in severely injured human subjects - Simmons, Jon D; Lee, Yann-Leei; Mulekar, Sujata; Kuck, Jamie L; Brevard, Sidney B; Gonzalez, Richard P; Gillespie, Mark N; Richards, William O (Annals of surgery, 2013)
Our objective was to execute a prospective cohort study to determine relationships between plasma mtDNA DAMP levels and the occurrence of systemic inflammatory response syndrome (SIRS), multiple organ dysfunction syndrome (MODS), and mortality. Mitochondrial DNA damage-associated molecular patterns (DAMPs) accumulate in the circulation after severe injury. Observations in animal models demonstrate that mtDNA DAMPs contribute to organ dysfunction; however, the link between plasma mtDNA DAMPs and outcome in severely injured human subjects has not been established. DNA was isolated from plasma samples taken from severely injured patients at hospital days 0, 1, and 2. Real-time PCR was used to quantify selected ≈200 base pair sequences of mtDNA within the COX1, ND1, and ND6 genes, as well as from the D-Loop transcriptional regulatory region. MODS was defined as a Denver Multiple Organ Failure score of 4 or greater. MtDNA DAMPs were quantified as PCR threshold cycle number. Lower threshold cycles indicate increased mtDNA DAMP content. Patients with SIRS had significantly increased mtDNA DAMP levels in all 4 sequences examined (32.14 ± 0.90 vs 29.00 ± 1.15 for COX1, 31.90 ± 0.47 vs 30.16 ± 1.42 for ND1, 32.40 ± 0.61 vs 28.94 ± 1.13 for ND6, and 33.12 ± 0.83 vs 28.30 ± 1.14 for D-Loop). Patients who developed MODS also had elevated mtDNA DAMP levels compared with those who did not (32.57 ± 0.74 vs 27.12 ± 0.66 for COX1, 32.45 ± 0.65 vs 28.20 ± 0.73 for ND1, 32.52 ± 0.56 vs 27.60 ± 0.79 for ND6, and 32.85 ± 0.75 vs 27.86 ± 1.27 for D-Loop). Patients with above-median mtDNA DAMP levels had a significantly elevated relative risk for mortality. Four patients died secondary to severe MODS. These findings comprise the first observational evidence that plasma mtDNA DAMPs is associated with the evolution of SIRS, MODS, and mortality in severely injured human subjects.